SERVICE LEARNING IN DATARAN MERDEKA AND LEARN THE HERITAGE OF KUALA LUMPUR, MALAYSIA - Satriadi Satriadi; Shahril Budiman; Junriana Junriana; Raja Abumanshur Matridi; Elvi Lastriani; Mia Muchia Desda (PT. Jurnal Center Indonesia Publisher, 2026)
Dataran Merdeka holds profound national and historical value as the site where Malaya’s independence was proclaimed in 1957, yet tourists’ understanding of its historical and architectural significance remains superficial. This community service activity aims to enhance the historical literacy of visitors and foster the involvement of local stakeholders in heritage conservation through educational media and participatory mentoring tailored to community needs. The implementation stages include observation to identify tourists’ information needs and the role of local actors, the development of contextually appropriate historical educational materials, direct engagement with visitors, and capacity-building for local vendors and guides as independent cultural informants. Results indicate increased tourist interest in historical narratives, observable shifts in visitor behavior toward greater cultural appreciation, and active participation of local business actors in disseminating heritage information. This program is expected to contribute to enriching tourism experiences, strengthening community capacity, and supporting sustainable heritage preservation through collaboration among visitors, local enterprises, and educational institutions.